Odpowiedzi

2009-11-22T20:07:46+01:00
(x+1)(x-2)+ (x+2)(x-1)=x²-2+x²-2=2x²-4
(5k+n)(k-2n)-k(4k+n)=5k²-10kn+nk-2n²-4k²-kn=k²-11kn+nk-2n²
(4+3)(y-2)-2y(4-2y)=4y-8+3y-6-8y+4y²=-y-14+4y²
-(3c-2)(c-1)-c(c-2)= 3c²-3c+2c-2+c²+2c=4c²+c-2
2(3a²-1)-(a+2)(a+2)=6a²-2-a²+4=5a²+2
5x²(x²+1)-(x²-2)(x²+3)=5x^4+5x²-x^4-6=4x^4+5x²-6

^4-do potęgi 4
2009-11-22T20:15:38+01:00
Najlepsza Odpowiedź!
2009-11-22T20:24:38+01:00
(x+1)(x-2)+ (x+2)(x-1)=x²-2+x²-2=2x²-4

(5k+n)(k-2n)-k(4k+n)=5k²-10kn+nk-2n²-4k²-kn = k²-11kn+nk-2n²

(4+3)(y-2)-2y(4-2y)=4y-8+3y-6-8y+4y² = -y-14+4y²

-(3c-2)(c-1)-c(c-2)= 3c²-3c+2c-2+c²+2c = 4c²+c-2

2(3a²-1)-(a+2)(a+2)=6a²-2-a²+4 = 5a²+2

5x²(x²+1)-(x²-2)(x²+3)=5x⁴+5x²-x⁴-6 = 4x⁴+5x²-6